Negative association of acetate with visceral adipose tissue and insulin levels - Layden BT (Dove Medical Press, 2012)
Brian T Layden1, Sudha K Yalamanchi1, Thomas MS Wolever2, Andrea Dunaif1, William L Lowe Jr11Division of Endocrinology, Metabolism and Molecular Medicine (BTL, SKY, AD, WLL), Northwestern University Feinberg School of Medicine, Chicago, Illinois, USA; 2Department of Nutritional Sciences (TMSW), University of Toronto, Toronto, CanadaBackground: The composition of gut flora has been proposed as a cause of obesity, a major risk factor for type 2 diabetes. The objective of this study was to assess whether serum short chain fatty acids, a major by-product of fermentation in gut flora, are associated with obesity and/or diabetes-related traits (insulin sensitivity and secretion).Methods: The association of serum short chain fatty acids levels with measures of obesity was assessed using body mass index, computerized tomography scan, and dual photon X-ray absorptiometry scan. Insulin sensitivity and insulin secretion were both determined from an oral glucose tolerance test and insulin sensitivity was also determined from a hyperinsulinemic euglycemic clamp.Results: In this population of young, obese women, acetate was negatively associated with visceral adipose tissue determined by computerized tomography scan and dual photon X-ray absorptiometry scan, but not body mass index. The level of the short chain fatty acids acetate, but not propionate or butyrate, was also negatively associated with fasting serum insulin and 2 hour insulin levels in the oral glucose tolerance test.Conclusions: In this population, serum acetate was negatively associated with visceral adipose tissue and insulin levels. Future studies need to verify these findings and expand on these observations in larger cohorts of subjects.Keywords: obesity, insulin, gut flora, short chain fatty acids